Influence of patient perceived relationship with pharmacist and physician and its association with beliefs in medicine. Issue 2 (8th March 2017) - Sansgiry, Sujit S.; Bhansali, Archita H.; Mhatre, Shivani K.; Sawant, Ruta V.
Abstract: Objectives: The purpose of this study was to evaluate the association between patients' perceived relationship with their pharmacist and physicians and its association with their beliefs in medicine. Methods: A cross‐sectional design was used and 307 self‐administered surveys were collected from adults, 45 years and above, in Houston, Texas via convenience sampling. Participants reported their general beliefs in medicine (perceived harm, perceived benefit and perceived medication overuse), perceived patient–pharmacist relationship, and perceived patient–physician relationship using a previously validated instrument adapted for this research. Perceived relationship constructs consisted of three domains each for pharmacist and physicians, namely trust/satisfaction, information sharing and patient involvement in treatment. Key findings: The study participants were white (46.25%) females (54.72%) with a mean age of 58 (±13) years. The results indicate that the participants trusted and were satisfied with both their pharmacist and physician. Participants with higher trust/satisfaction with pharmacist consider medications as more beneficial. While participants with higher trust/satisfaction with their physicians were less likely to believe that doctors over‐prescribe medicines, which may lead to medication over use. Information sharing by pharmacists was associated with a significant decrease in perception of general benefits of medications. Further participant's involvement in treatment decisions by the physician had a significant association with increased perceptions of benefits of medications. Conclusions: Patients trust/satisfaction with their pharmacist leads to the belief that medications are more beneficial while a higher trust/satisfaction with physicians leads to lower beliefs in medicine, especially patients less likely to be adherent with appropriate medications.